Pengaruh Kualitas Layanan terhadap Customer Loyalty pada Starbucks Coffee di Wilayah Bandung - Linda Ayu Puspitasari; Gandhi Pawitan (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to determine the effect of service quality on customer loyalty at Starbucks Bandung City. The population and sample used in this study are people who have bought Starbucks in Bandung. the Total of respondents collected in this study were 110 people. The method used to collect data is a questionnaire through Google forms. Data analysis techniques were performed using simple regression analysis using the Statistical Program Social Science (SPSS) software version 29. The results of this study found that there was a significant positive effect of service quality on customer loyalty.